2012
DOI: 10.1242/dev.080051
|View full text |Cite
|
Sign up to set email alerts
|

Motoneuronal Sema3C is essential for setting stereotyped motor tract positioning in limb-derived chemotropic semaphorins

Abstract: SUMMARYThe wiring of neuronal circuits requires complex mechanisms to guide axon subsets to their specific target with high precision. To overcome the limited number of guidance cues, modulation of axon responsiveness is crucial for specifying accurate trajectories. We report here a novel mechanism by which ligand/receptor co-expression in neurons modulates the integration of other guidance cues by the growth cone. Class 3 semaphorins (Sema3 semaphorins) are chemotropic guidance cues for various neuronal proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…We found, that CD271 knock-down abolished the capacity of melanoma cells to form heterogeneous tumors most likely due to down-regulation of mediators of melanoma invasion and metastasis ( GLI-2 [21], SOX2 [22] and ERBB3 [23]), angiogenesis ( IGFBP-2 [24]), proliferation ( FST [25] and MITF ) or chemoresistence ( RHOJ [26]). In addition, GSEA revealed that some of these genes are crucial for NCSC maintenance and migration, like SOX10 and SNAI2 or SEMA3C [27], respectively. We found SOX10 as one of the most down-regulated genes in CD271 k.d.…”
Section: Discussionmentioning
confidence: 99%
“…We found, that CD271 knock-down abolished the capacity of melanoma cells to form heterogeneous tumors most likely due to down-regulation of mediators of melanoma invasion and metastasis ( GLI-2 [21], SOX2 [22] and ERBB3 [23]), angiogenesis ( IGFBP-2 [24]), proliferation ( FST [25] and MITF ) or chemoresistence ( RHOJ [26]). In addition, GSEA revealed that some of these genes are crucial for NCSC maintenance and migration, like SOX10 and SNAI2 or SEMA3C [27], respectively. We found SOX10 as one of the most down-regulated genes in CD271 k.d.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that the combined expression of class 3 semaphorins is present in the chick forelimb, and that Sema3C is involved in the pathfinding of spinal motor neurons (Sanyas et al . ). Thus, to confirm the role of class 3 semaphorins during amniote limb development, further expression analyses of Sema3C are necessary.…”
Section: Discussionmentioning
confidence: 97%
“…Among them, class 3 semaphorin family molecules, which act as a repulsive cue for developing axons, play important roles in the pathfinding of limb‐innervating neurons (Bonanomi & Pfaff ; Sanyas et al . ). In particular, knockout mice for Sema3A or its receptor (neuropilin1) exhibit incorrect innervation of spinal axons in the limb bud (Kitsukawa et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is accumulating evidence that these families of proteins function in the specifi cation of motor axon trajectory in the limb (Huber et al 2005 ;Moret et al 2007 ;Huettl et al 2011 ;Sanyas et al 2012 ). Interestingly, since semaphoring-neuropilin signaling has been previously implicated in cortical neuron migration (Chen et al 2008 ), it would not be at all surprising if such signaling also impacts spinal motor neuron soma localisation, although so far no evidence of this function has been reported.…”
Section: Other Cell Surface Effectorsmentioning
confidence: 99%